2009
DOI: 10.1007/s11547-009-0403-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of MDCT coronary angiography in patients referred for heart valve surgery

Abstract: The diagnostic accuracy of 64-row CTCA for ruling out the presence of significant coronary stenoses in patients undergoing valve surgery is excellent and allows CTCA to be used as a gatekeeper for invasive CCA in these patients. MDCT is a necessary preoperative examination that provides useful information for identifying potential operative complications of surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Thirty-four full-text reports were selected for further evaluation, from which 17 studies were excluded for the following reasons: no systematic ICA was performed (9 papers)-it was either completely absent (31,32) or was used only to confirm abnormal and/or nondiagnostic CTA findings (33)(34)(35)(36)(37)(38)(39); data to calculate diagnostic accuracies were not provided or could not be derived (4 papers) (40)(41)(42)(43); no reference to valve surgery was present (1 paper) (43); and a heterogeneous patient population inclusive of patients without VHD was included (4 papers) (44)(45)(46)(47) or no values for true-positive and false-negative observations were reported (i.e., variance is infinite and CIs as well as sensitivity could not be computed) (2 papers) (44,45). Seventeen studies were included in the final analysis ( years; 61% male) at least a 64-slice CTA was used (4,7,8,10,11,13,14,(18)(19)(20), whereas 7 studies evaluated 16-or 40-slice CTA in a total of 392 patients (mean age 68.0 AE 3.1 years; 59% male) (5,6,9,12,(15)(16)(17). All studies reported a $50% stenosis cutoff to determine the presence of significant CAD (in 1 study that originally used a $70% stenosis cutoff, the corresponding author was approached to provide supplementary accuracy data for $50% stenosis cutoff) (10).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-four full-text reports were selected for further evaluation, from which 17 studies were excluded for the following reasons: no systematic ICA was performed (9 papers)-it was either completely absent (31,32) or was used only to confirm abnormal and/or nondiagnostic CTA findings (33)(34)(35)(36)(37)(38)(39); data to calculate diagnostic accuracies were not provided or could not be derived (4 papers) (40)(41)(42)(43); no reference to valve surgery was present (1 paper) (43); and a heterogeneous patient population inclusive of patients without VHD was included (4 papers) (44)(45)(46)(47) or no values for true-positive and false-negative observations were reported (i.e., variance is infinite and CIs as well as sensitivity could not be computed) (2 papers) (44,45). Seventeen studies were included in the final analysis ( years; 61% male) at least a 64-slice CTA was used (4,7,8,10,11,13,14,(18)(19)(20), whereas 7 studies evaluated 16-or 40-slice CTA in a total of 392 patients (mean age 68.0 AE 3.1 years; 59% male) (5,6,9,12,(15)(16)(17). All studies reported a $50% stenosis cutoff to determine the presence of significant CAD (in 1 study that originally used a $70% stenosis cutoff, the corresponding author was approached to provide supplementary accuracy data for $50% stenosis cutoff) (10).…”
Section: Resultsmentioning
confidence: 99%
“…In the majority of such patients, pre-operative evaluation for coronary artery disease (CAD) with invasive coronary angiography (ICA) is recommended (1,2), although most patients are found to have no significant coronary stenoses (3). In recent years, several studies have tested the diagnostic performance of coronary computed tomography angiography (CTA) in patients undergoing cardiac valvular surgical treatment (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). However, all of these studies were limited by small sample sizes in single centers, which may introduce bias that obfuscates the actual diagnostic performance of coronary CTA compared with ICA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the ability of planning ICA and/or percutaneous coronary intervention based on CTA data sets in case of a positive observation is clearly advantageous with regard to shortening the procedural time and limiting the use of contrast dye. To date, the utility of CTA for the identification of significant CAD in patients with severe aortic stenosis has been investigated almost exclusively prior to open heart surgery [15][16][17][18]. Most of these studies using 64-detector CTA technology were limited to a small number of highly selected patients and reported variable sensitivities between 68 and 100 % with specificities between 81 and 91 % for the detection of significant CAD.…”
Section: Discussionmentioning
confidence: 99%
“…1 In patients with severe mitral regurgitation referred for cardiac surgery, cardiac computed tomography (CT) has been used to screen patients for coronary artery disease. 2 Data are limited on the role of CT in the assessment of anatomic abnormalities of the mitral valve. 3,4 We undertook this study to determine whether dual-source 64-slice multidetector computed tomography (DSCT) could be used to determine the specific mechanism of degenerative mitral regurgitation in patients undergoing surgical mitral valve repair.…”
Section: Introductionmentioning
confidence: 99%